Graceling [compact disc, unabridged] - Cashore, Kristin (Cashore, Kristin. Graceling Realm book., 2009)
In a world where some people are born with a unique and sometimes uncanny gift, Katsa was certainly no exception. At an early age, she demonstrated an uncomfortable gift for killing. This makes her the perfect tool for her uncle, King Randa. But Katsa detests being used and decides to stand against the injustice surrounding her.